Uganda's oil: How much, when, and how will it be governed? - Sebastian Wolf; Vishal Aditya Potluri (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We study Uganda's journey to become a petroleum producer and provide estimates regarding the size and timing of the oil revenues to be expected. At an average US38 per capita per year over a 33-year period, oil revenue by itself will not be transformational for the Ugandan economy, but it could provide a welcome boost. The question is whether the Ugandan government will manage to avoid squandering it, and will transform the country's natural resource assets into productive assets. To this end, the government has made significant additions and changes to the policy and institutional framework that will govern the use of revenues, adapted from the Norwegian model. We study the framework put in place and identify a number of potential shortcomings. Weaknesses in public investment management further raise doubts about the transformational impact of the planned investments.
Keywords: O13; O55; 330; Uganda; extractive industries; structural change